KEPASTIAN HUKUM DALAM PERJANJIAN JUAL BELI KOMPONEN OTOMOTIF ANTARA SUPPLIER DAN PERUSAHAAN: EMPIRICAL LEGAL STUDIES PT BONECOM TRICOM PADA KEGIATAN INDUSTRI RANTAI PASOK OTOMOTIF INDONESIA - Ilham, Junaidi; Tanjung, Afriansyah; Maulida, Arum Anggraeni (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2025)
Research objectives to analyze the law of sale and purchase agreements for goods in the automotive component industry based on the Civil Code (KUH Perdata) to provide legal certainty. This study uses Empirical Legal Studies , combining normative legal research, which focuses on literature studies, legislation, and legal principles related to the law of obligations and valid agreement requirements , with empirical legal research, which includes interviews and analysis of general cooperation agreements. The novelty of this research lies in adapting and developing a specific agreement relevant to the automotive component industry , moving beyond the general provisions of Article 1457 of the Civil Code to comprehensively regulate the rights and obligations of both parties, thereby acting as a solution for legal certainty in the supply chain. Findings show that implementing a clear and specific 16-article component Sale and Purchase Agreement in PT Bonecom Tricom's transactions with its suppliers, particularly those that fulfill the requirements of Article 1320 of the Civil Code , has a significant positive impact on supplier performance. For instance, a comparison of five target suppliers in the period January–June 2024 and January–June 2025 indicated an average performance increase of 0.18 points. This indicates that clear legal stipulations effectively improve compliance and performance in quality and delivery. The concludes that the Component Sale and Purchase Agreement successfully serves as a binding legal instrument to ensure legal certainty and is a concrete measure to enhance supplier performance within the company's supply chain. Keywords: Legal Certainty; Sale and Purchase Agreement; Automotive Component; Supplier Performance; Civil Code